Nutritional and Medicinal value of the edible stinkbug, Encosternum delegorguei Spinola consumed in the Limpopo Province of South Africa and its host plant Dodonaea viscosa Jacq. var. angustifolia - Toms, R.B. (University of Pretoria, 2013)
Thesis (PhD (Paraclinical Science))--University of Pretoria, 2006.